Adult hippocampal neurogenesis: A coming-of-age story - Kuhn, H. Georg; Toda, Tomohisa; Gage, Fred H. (Journal of Neuroscience, 2018)
What has become standard textbook knowledge over the last decade was a hotly debated matter a decade earlier: the proposition that new neurons are generated in the adult mammalian CNS. The early discovery by Altman and colleagues in the 1960s was vulnerable to criticism due to the lack of technical strategies for unequivocal demonstration, quantification, and physiological analysis of newly generated neurons in adult brain tissue. After several technological advancements had been made in the field, we published a paper in 1996 describing the generation of new neuronsint headultrat brainand the decline of hippocampal neurogenesis duringaging.Thepaper coincided with the publication of several other studies that together established neurogenesis as a cellular mechanism in the adult mammalian brain. In this Progressions article, which is by no means a comprehensive review, we recount our personal view of the initial setting that led to our study and we discuss some of its implications and developments that followed. We also address questions that remain regarding the regulation and function of neurogenesis in the adult mammalian brain, in particular the existence of neurogenesis in the adult human brain.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Adult neurogenesis; Aging; Dentate gyrus; Hippocampus